(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
The text presents edition no. 28 of Móin-Móin -Magazine of Studies in the Arts of Puppetry, with the theme "African and Afrodiasporic Puppet Theater”, its context of composition, the questions that provoked the authors and the invitation to read the published articles.